2001
DOI: 10.1097/00042737-200111000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Should anti-Helicobacter therapy be different in patients with dyspepsia compared with patients with peptic ulcer diathesis?

Abstract: Physicians should try to reach an optimal cure rate with initial anti-Helicobacter therapy. Helicobacter pylori infection in patients with peptic ulcer disease (PUD) is more likely to be cured then in patients with 'functional' dyspepsia (FD). Differences in cure rates of 5-15% are usually reported, which is considered to be clinically relevant. Different strains (virulent v. non-virulent) in PUD and FD may induce different alterations in the gastric mucosa, and thereby either facilitate or impair antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Similarly, no difference in eradication success was observed between the 7 and 10 days protocols [8,11]. This has not been confirmed by all authors [9], probably due to the smaller number of patients studied or the high overall eradication success, as pointed out by de Boer et al [14]. Some of the published data indicate that eradication success depends on the proportion of patients with nonulcer dyspepsia included in the analysis [5,10].…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, no difference in eradication success was observed between the 7 and 10 days protocols [8,11]. This has not been confirmed by all authors [9], probably due to the smaller number of patients studied or the high overall eradication success, as pointed out by de Boer et al [14]. Some of the published data indicate that eradication success depends on the proportion of patients with nonulcer dyspepsia included in the analysis [5,10].…”
Section: Discussionmentioning
confidence: 88%
“…Some authors [37,38] have reported that the frequency of H. pylori eradication is higher in patients with PUD than in those with NUD, although this evidence has not been confirmed by other investigators, probably on account of the small number of patients studied or the high overall eradication rates, as pointed out by de Boer et al. [39]. However, in the present study conducted on a large number of patients and with a submaximal eradication rate, a comparable percentage of patients with PUD, NUD, or GERD were found to be cured of H. pylori infection.…”
Section: Discussionmentioning
confidence: 96%
“…35 The difference of H. pylori strain in patients with peptic ulcer and functional dyspepsia may induce the biased result of eradication rate. First, there was the absence of antimicrobial susceptibility testing and culturing, because antibiotic resistance is the most important cause of treatment failure.…”
Section: Discussionmentioning
confidence: 99%